Unique presentation of T-cell/histiocyte-rich large B cell lymphoma complicated with hemophagocytic lymphohistiocytosis: case report and review of the literature - Pešić, Andrej; Vuković, Vojin; Kozarac, Sofija; Otašević, Vladimir; Bibić, Tamara; Mihaljević, Biljana; Antić, Darko (Journal of Medical Biochemistry, 2024)
Hemophagocytic lymphohistiocytosis (HLH) is a rare, life-threatening hyperinflammatory disorder characterized by dysfunction of NK cells and cytotoxic lymphocytes. We present a rare case of a patient diagnosed with HLH who presented with persistent fever during treatment for refractory T-cell/histiocyte-rich large B-cell lymphoma (TCHRBCL), highlighting the challenges of managing HLH in the context of refractory lymphoma. According to our review of the literature, this is the first case of HLH that developed several months into treatment for refractory TCHRBCL and not in close temporal relation to lymphoma diagnosis.